Strategic Management and Organizational Adaptation in Modern Agribusiness: Bridging the Gap Between Strategy, Structure, and Resilience - Usman, Marsam; Bandera, Abdani; Usman-Macadaag, Omaimah; Macadato, Nasibah (Indonesian Journal Publisher, 2025)
Modern agribusiness operates in an increasingly complex and uncertain environment, characterized by systemic risks such as climate change, extreme weather events, disease outbreaks, regulatory shifts, and volatile market dynamics. These multi-vector disruptions propagate through value chains, amplifying volatility and challenging long-term planning. Traditional strategic management frameworks emphasizing efficiency, competitive positioning, and core competencies are inadequate for sustaining performance under such uncertainty. Contemporary literature advocates a multi-faceted strategic orientation that integrates market sensitivity, innovation, and disciplined planning to reconcile short-term operational goals with long-term resilience. This study employs a systematic literature review of peer-reviewed journals, industry reports, and authoritative organizational studies published between 2010 and 2025, examining strategic management, organizational adaptation, and resilience measurement in agribusiness. The analysis identifies persistent gaps, including the limited operationalization of resilience metrics, underdeveloped frameworks for embedding non-market risk management into organizational structures, and insufficient integration of non-financial expertise into decision-making. Findings indicate that hybrid organizational designs—balancing centralized coordination with decentralized decision-making—combined with digitalization and networked information systems, enhance traceability, responsiveness, and coordination across value chains. Governance professionalization in family-owned agribusinesses improves accountability, strategic oversight, and systematic risk management, while aggregation models address market fragmentation, improve resource access, and facilitate scalable resilience investments. Overall, bridging strategy, structure, and measurable resilience requires an integrated approach that combines quantitative metrics, adaptive organizational structures, professionalized governance, and cooperative aggregation mechanisms. This conceptual synthesis offers actionable guidance for managers and researchers seeking to enhance adaptive capacity, operational efficiency, and long-term value creation in modern agribusiness, highlighting the need for empirical studies to quantify the impacts of these integrated strategies.